An application of the Sidek module development in rebt counseling intervention module design for orphans - Madihie, Amalia; Mohd Noah, Sidek (Elsevier, 2013)
This article introduces Rational Emotive Behavior Therapy Self-Concept for Adolescents (REBT-SC-A). The main objective of this REBT-SC-A is to assist orphans in Malaysia to develop a positive and healthy self-concept. The Sidek Module Development Model (SMDM) and Rational Emotive Behavior Therapy theory are applied as a guideline in developing REBT- SC-A. A validation stage was carried out by five expert counselors, and Cronbach alpha .80 was obtained. A group of orphans from aged 13 to 17 years was piloted to check the module's reliability and the Cronbach alpha .93 was obtained. Implications of the study are discussed later in the article.